Comparing educational interventions: Correcting misperceived norms improves college students' mental health attitudes. Issue 1 (16th November 2017) - Turetsky, Kate M.; Sanderson, Catherine A.
Abstract: This research targeted potential psychological contributors to college students' low levels of help‐seeking for mental distress using a field experiment. Researchers randomly assigned 520 undergraduates to 15‐min interventions: a novel, theory‐driven social norms intervention correcting misperceived distress, stigma, and help‐seeking norms; a general education intervention increasing mental health awareness; and a stress management active control condition. The norms intervention instilled more accurate perceptions of mental health norms and temporarily reduced perceived public stigma compared to other conditions. The norms and general education interventions improved attitudes toward seeking help for mental distress for at least 2 months, relative to the control. Effects on help‐seeking behavior were not observed in this timeframe. This research elucidates the robustness of brief social psychological mental health interventions on college campuses.